Analisis Perbandingan Kinerja Keuangan Perusahaan Antara Menggunakan Rasio Profitabilitas Dengan Economic Value Added ( Studi Kasus Pada Perusahaan Astra International TBK Periode Tahun (2012 - 2015 ) - NURJANAH, HANI DEWI; , Muhammad Sholahuddin, S.E, Msi (2017)
This study aimed to measure is to know the company's financial performance with using the Ratio of Profitability and Economic Value Added as well as knowing how the comparison between the application of profitability ratio analysis and methods of EVA as a measure of financial performance. This type of research used in this researh is descriptive using a quantitative approach. The population in this research was PT Astra International Tbk. The samples used in form of data PT Astra International Tbk first quarter 2012-fourth quarter 2015 and annual report year period 2012-2015. Based on the results of the research explained that the results of the company's financial performance is measured by the analysis of profitability ratios of Net Profit Margin, Return On Equity, and Return On Assets has decreased every year. While Economic Value Added increased during four periods and generate a positive EVA value (EVA > 0). The results of t test analysis of comparative analysis of profitability ratios such as NPM, ROE, and ROA on EVA showed a significant difference. The results of the overall study concluded their financial performance measured difference between using a method of analysis of profitability and economic value added (EVA). These differences are not accounting for their cost of capital in the ratio of profitability. Then the EVA method is considered superior in evaluating the company's financial performance to achieve the expectations of the shareholders. Keyword: Financial Performance, Profitability Ratio, Economic Value Added